Analisis Model Regresi Ketepatan Waktu Vaksinasi Meningitis Pada Jamaah Umrah di Balai Kekarantinaan Kesehatan Kelas I Samarinda - Alwan Zakki Nozomi; Irfansyah Baharuddin Pakki; Akhmad Azmiardi; Ratno Adrianto; Ida Ayu Indira Dwika Lestari; Yadi Yadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Timeliness of meningitis vaccination among Umrah pilgrims remains an important public health issue due to the high risk of Neisseria meningitidis transmission during umrah activities. Although meningitis vaccination is a mandatory requirement for Umrah pilgrims, many individuals still receive the vaccine close to their departure date, resulting in suboptimal immune protection. This study aimed to analyze the factors associated with the timeliness of meningitis vaccination among Umrah pilgrims at the Health Quarantine Office Samarinda in 2026. A quantitative study with a cross-sectional design was conducted involving 306 respondents selected through purposive sampling. Data were collected using structured questionnaires and vaccination records, then analyzed using univariate, bivariate, and multivariate logistic regression analyses. The findings revealed that individual factors, including knowledge, perceived susceptibility, perceived severity, perceived benefits, and attitudes, were significantly associated with vaccination timeliness. External factors such as access to information, travel agent support, and family support, as well as structural factors including distance accessibility, procedural convenience, and availability of health facilities, also demonstrated significant associations with timely vaccination. Multivariate analysis identified the most dominant factor influencing vaccination timeliness among Umrah pilgrims. The study concludes that the timeliness of meningitis vaccination is influenced by a combination of individual, social. Keywords : meningitis vaccination, timeliness, Umrah pilgrims.